The effect of residue management on the nutrient cycle in the production of rooibos (Aspalathus linearis) at Nieuwoudtville, Northern Cape - Nieuwoudt, Stephanus Francois (Stellenbosh : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.